Effect of Egg Rearing Temperature and Storage Time on the Biological Characteristics of the Predatory Stink Bug Podisus nigrispinus (Hemiptera: Pentatomidae) - Vacari, Alessandra M. [UNESP]; Goulart, Roberto M. [UNESP]; Volpe, Haroldo X. L. [UNESP]; De Bortoli, Sergio A. [UNESP] (Entomological Soc Amer, 2014)
In this study, we investigated the effect of egg rearing temperature and storage time on biological characteristics of the predatory stink bug Podisus nigrispinus (Dallas). In a preliminary experiment, eggs were incubated at 5, 10, 15, and 20 degrees C to examine the effect of rearing temperature on egg development. From this, we found that 15 degrees C was the optimal temperature for egg storage. To examine the effect of storage period on biological characteristics, eggs were stored at 15 +/- 1 degrees C for 0 (control), 1, 5, 9, 13, or 17 d, and then maintained at 25 degrees C, allowing us to determine the effect of storage period on incubation period and egg viability. Once nymphs reached the second instar, they were kept in individual petri dishes, and we examined the effect of storage period on stadial length, nymphal viability, and weight of fifth-instar nymphs. Finally, when the nymphs reached the adult phase, we measured the effect of storage period on adult longevity, neonate adult weight, fecundity, and egg hatching success. Our results showed that the storage of eggs at 15 +/- 1 degrees C for periods of up to 17 d did not significantly affect most of the biological characteristics analyzed.
Keywords: Asopinae; Biological control; Biology of insects